Evaluating determinants of receipt of molecular imaging in biochemical recurrent prostate cancer. (28th November 2020) - Borno, Hala T.; Kuo Lin, Tracy; Odisho, Anobel Y.; Desai, Arpita; Koshkin, Vadim; Werner, Kalin; Legaspi, Nichole; Bucknor, Matthew; Bell, Alexander; Zhang, Sylvia; Hope, Thomas A.
Abstract: Background: Molecular imaging with novel radiotracers is changing the treatment landscape in prostate cancer (PCa). Currently, standard of care includes either conventional and molecular imaging at time of biochemical recurrence (BCR). This study evaluated the determinants of and cost associated with utilization of molecular imaging for BCR PCa. Methods: This is a retrospective observational cohort study among men with BCR PCa from June 2018 to May 2019. Multivariate logistic regression models were employed to analyze the primary outcome: receipt of molecular imaging (e.g. Fluciclovine PET and Prostate Specific Membrane Antigen PET) as part of diagnostic work‐up for BCR PCa. Multivariate linear regression models were used to analyze the secondary outcome: overall healthcare cost within a 1‐year time frame. Results: The study sample included 234 patients; 79.1% White, 2.1% Black, 8.5% Asian/Pacific Islander, and 10.3% Other. The majority were 55 years or older (97.9%) and publicly insured (74.8%). Analysis indicated a one‐unit reduction in PSA is associated with 1.3 times higher likelihood of receiving molecular imaging ( p  < 0.01). Analysis found that privately insured patients were associated with approximately $500, 000 more in hospital reimbursement ( p  < 0.01) as compared to the publicly insured. Additionally, a one‐unit increase in PSA is associated with $6254 increase in hospital reimbursement or an increase in total payments by 2.1% ( p  < 0.05). Conclusions: Higher PSA was associated with lower likelihood for molecular imaging and higher cost in a one‐year time frame. Higher cost was also associated with private insurance, but there was no clear relationship between insurance type and imaging type. Abstract : This study evaluated the determinants of and cost associated with utilization of molecular imaging for biochemically recurrent prostate cancer. Higher prostate‐specific antigen level was associated with lower likelihood for molecular imaging and higher cost in a 1‐year timeframe.